PENGARUH ABU AMPAS TEBU SEBAGAI FILLER PENGGANTI TERHADAP KARAKTERISTIK MARSHALL CAMPURAN SUPERPAVE - Fauziah, Miftahul; Kushari, Berlian; Ranski, Fauzan (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
The increasing development and maintenance of pavement infrastructure result in increasing demand for materials to be used, including the fillers. The use of fillers in asphalt concrete mixtures is very limited in amount but contributes to considerable effects on the performance of the mixtures. A general problem faced in the production of fillers obtained from stone crushing is that it can only produce a substantially less volume than needed; hence the efforts to find alternative sources for fillers. Bagasse ashes are one of solid residual wastes produced as the byproduct of the process of sugar cane heating. This paper presents the results of laboratory works devoted to evaluating the use of bagasse ashes as fillers in a Superpave mixture. Laboratory tests were carried out in three stages. Firstly, physical property tests were run. Secondly, a series of optimum bitumen content for mixtures with 0%, 25%, 50%, 75%, and 100% of bagasse ashes portion to the total portion of fillers were determined respectively. Lastly, Marshall Characteristics were measured and immersion tests were conducted upon the mixtures. Results showed that, in general, sampled bagasse ashes were suitable as fillers for the Superpave mixture. The greater the percentage of bagasse ashes corrensponds to the lower values of stability, VITM, VMA, and the higher values of flow, VFWA, MQ and Index of Retained Strength. Higher proportion of bagasse ashes requires higher optimum bitumen content.